IMPLEMENTASI KONSEP RUMAH ISLAMI PADA PERUMAHAN DI MARTAPURA - Nurul Hidayati (Lambung Mangkurat University Press, 2018)
In the last few years, the construction of simple houses (types 36 m2 and 45 m2) has been increasingly widespread. No exception in Martapura city, which is also known as the Veranda of Mecca. Because Martapura city is a religious city, it has an indirect impact on the behavior patterns of its people who have an Islamic lifestyle and Islamic culture, such as: a way of dressing that is more closed, behaves well in social relations and in public places. In fact, most of the events held come from Islamic culture and Islamic themes. However, has the arrangement of simple house space in the housing complex in Martapura already been of an Islamic concept? The research objective is to analyze how much Martapura community knowledge about the concept of Islamic houses, make an example of a house plan with an Islamic concept and calculate the cost of constructing a modest house with an Islamic concept. For this reason, this research conducted a survey using instruments in the form of questionnaires as primary data. By measuring the community's knowledge about the concept of Islamic houses, the characteristics of the respondent's house (spatial planning), and plans to renovate existing homes into houses with an Islamic concept. The research samples are 300 people as questionnaire respondents. The data analyzed by using descriptive analysis.The results showed that the knowledge of the Martapura community about the basic concept of an Islamic house and the characteristics of the Islamic house are still low. Similarly, the arrangement of housing space in Martapura houses are still not in accordance with the concept of Islamic homes. Even though the house layout of the Islamic concept is not too different from the house that was usually built by the developer. And the difference between the construction costs is not too large. For a simple house type 36 with a land area of ​​100 m2-120 m2 the difference in cost is only around Rp. 1.3 million - Rp. 1.5 million. As for a simple house type 45 with an area of ​​140m2 the difference in cost is only around Rp. 1.8 million.